Clinical and Radiographic comparative evaluation of buccal and palatal corticotomy with buccal corticotomy in periodontally accelerated osteogenic orthodontics with surgical bur - Pavankumar Addanki; Jagadish Reddy Gooty; Rajababu Palaparthy (Wolters Kluwer Medknow Publications, 2017)
Background: Periodontally accelerated osteogenic orthodontics is a clinical procedure that combines selective corticotomy, particulate grafting, and application of orthodontics. It reduces treatment time, increases stability of teeth, and prevents relapse of orthodontic tooth moment. The present study was aimed to explore the clinical and radiographic comparison of bone density changes, retraction time differences in buccal and palatal corticotomy with buccal corticotomy which was done by surgical bur. Materials and Methods: A split-mouth was designed in 16 patients and divided into right (buccal and palatal corticotomy) (Group I), left (buccal corticotomy) (Group II) sides. In both groups, decortication was done with surgical bur. Clinical parameters such as gingival bleeding index and probing pocket depth were recorded at baseline, 1 month, 3 months, and 6 months. Bone density changes were measured by computed tomography at baseline and after 6 months after surgery and also used for evaluating differences in bone density changes between two groups. Retraction time differences were also measured in both groups. Results: In both groups, there was significant difference between bone density changes at baseline and 6 months after surgery. However, the difference between two groups was not significant. The difference in clinical parameters between two groups was not significant. The difference in retraction time differences was not significant. Conclusion: Within limits of the study, it may be concluded that there was difference between bone density changes before and 6 months after surgery. Difference in total treatment time found to be no significant between two groups.